Evaluating the bioreducing potential of the leaves, knobs and roots of Zanthoxylum capense (small knobwood) for the synthesis of silver nanoparticles, applicable to in vitro fungal contamination control. (29th August 2017) - Bodede, Olusola; Shaik, Shakira; Govinden, Roshini; Moodley, Roshila
Abstract: In this study we report on the green synthesis of silver nanoparticles using extracts from selected morphological parts of Zanthoxylum capense . UV–vis spectra of the biosynthesised silver nanoparticles (AgNPs) revealed absorption peaks at around 450 nm, indicative of the nanoparticles' surface plasmon resonance, whilst infrared vibrational frequencies indicated the presence of flavonoids, alkaloids, and free and bonded sugars which could be responsible for the reduction and stabilisation of the AgNPs. 1 H-NMR fingerprinting of the aqueous knob extract confirmed the active bio-reducing phytochemical of the knobs to be 6-O- p -coumaroyl- β -D-glucopyranoside. The nature, shape and morphology of the biosynthesised AgNPs were examined using transmission electron microscopy (TEM), selected area electron diffraction (SAED), scanning electron microscopy (SEM) and energy dispersive x-ray (EDX) analysis. Z. capense AgNPs were mostly spherical in shape with particle sizes in the range of 4–28 nm, 7–20 nm and 4–32 nm for leaves, knobs and roots, respectively. Leaf extracts were the most efficient in the synthesis of AgNPs with an average yield of 0.027 g AgNPs per g of plant (dry mass). The AgNPs were more effective than sodium hypochlorite (NaOCl) and sodium dichloroisocyanurate (NaDCC) in the control of in vitro fungal contamination in nodal explants of Z. capense up to two weeks. Shoots induced from the surface sterilised explants were further used for shoot multiplication on benzyl aminopurine (BAP) and kinetin (KIN). BAP at 0.5 mg l −1 gave the highest percentage (88.6%) of explants bearing shoots with an average of 4.78 shoots per explant. A total of 15 fungal endophyte strains associated with Z. capense were identified using molecular methods.